2020
DOI: 10.1084/jem.20192262
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification and characterization of infected cells in blood during chronic active Epstein-Barr virus infection

Abstract: Epstein-Barr virus (EBV) preferentially infects epithelial cells and B lymphocytes and sometimes T and NK lymphocytes. Persistence of EBV-infected cells results in severe lymphoproliferative disorders (LPDs). Diagnosis of EBV-driven T or NK cell LPD and chronic active EBV diseases (CAEBV) is difficult, often requiring biopsies. Herein, we report a flow-FISH cytometry assay that detects cells expressing EBV-encoded small RNAs (EBERs), allowing rapid identification of EBV-infected cells among PBMCs. EBV-infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 58 publications
4
45
1
Order By: Relevance
“…Recently, a new flow cytometry technique combining surface marker staining with in situ hybridization for the EBER RNAs has been developed. 41,42 Sequential examination of PB using this method, without dissecting mice, shall enable us to analyze the effects of bortezomib on EBV-infected cells in vivo in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a new flow cytometry technique combining surface marker staining with in situ hybridization for the EBER RNAs has been developed. 41,42 Sequential examination of PB using this method, without dissecting mice, shall enable us to analyze the effects of bortezomib on EBV-infected cells in vivo in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…Oko and coauthors concluded that this technique affords new opportunities to understand the complexity of virus infection within single cells when they observed that EBV infection (gamma herpesvirus infection in general) can be surprisingly heterogeneous at the level of the individual cell [ 82 ]. Using the PrimeFlow assay, very recently Fournier et al showed that during chronic active EBV infection, EBV-infected B cells from blood expressed PC differentiation markers [ 83 ]. Taking into consideration these achievements, the PrimeFlow assay may also be successful in EBV–periodontitis research.…”
Section: Advanced Prospective Methodsmentioning
confidence: 99%
“…The detection of EBV-DNA in each lymphocyte fraction isolated by antibody-conjugated magnetic beads is effective to determine the phenotypes of EBV-infected cells. Recently, a new flow cytometry technique combining surface marker staining with in situ hybridization for EBER RNAs has been developed [ 20 , 21 ]. Second, I want to argue the disease definition of systemic EBV-positive T-cell lymphoma of childhood.…”
Section: The Issues On the Who 2017 Classification Which Surfacedmentioning
confidence: 99%